2016
DOI: 10.1371/journal.pone.0157318
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea: A Cluster Analysis at Time of Diagnosis

Abstract: BackgroundThe classification of obstructive sleep apnea is on the basis of sleep study criteria that may not adequately capture disease heterogeneity. Improved phenotyping may improve prognosis prediction and help select therapeutic strategies. Objectives: This study used cluster analysis to investigate the clinical clusters of obstructive sleep apnea.MethodsAn ascending hierarchical cluster analysis was performed on baseline symptoms, physical examination, risk factor exposure and co-morbidities from 18,263 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
118
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 28 publications
3
118
1
3
Order By: Relevance
“…Variability in results can be expected, since the studies differed in the variables entered in the analyses. In addition, the studies are heterogeneous in the number of patients included, and only three studies were multicentric [89,90,93]. Finally, the complexity of OSA can affect the results.…”
Section: Clinical Phenotypes Of Osamentioning
confidence: 99%
See 2 more Smart Citations
“…Variability in results can be expected, since the studies differed in the variables entered in the analyses. In addition, the studies are heterogeneous in the number of patients included, and only three studies were multicentric [89,90,93]. Finally, the complexity of OSA can affect the results.…”
Section: Clinical Phenotypes Of Osamentioning
confidence: 99%
“…These authors identified four main clinical phenotypes, corresponding to increasing severity of OSA, and six clusters, with no OSA and mild OSA as single clusters, moderate and severe OSA each subdivided into two clusters according to the presence or absence of significant comorbidities. Two studies, the largest to date, were published in 2016 on OSA patients from two French registries [90,93]. BAILLY et al [90] identified six clusters in the French OSA registry (>18 000 patients), corresponding to patients of different ages, with variable OSA severity and comorbidity burdens.…”
Section: Clinical Phenotypes Of Osamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hypertension is increasingly recognised as an important predictor of prevalent OSA and appears to be more predictive than excessive day-time sleepiness in some settings [5]. However, recent evidence also indicates that only moderate-severe OSA (AHI >20 events·h -1 ) constitutes a significant independent risk for hypertension [2] and cluster analysis of sleep clinic populations indicates that particular population subtypes are especially associated with hypertension [6].These recent reports regarding the very high general prevalence of SDB and factors that influence the relationship with hypertension prompt a reassessment of the clinical relevance regarding the association between OSA and hypertension, especially nocturnal hypertension, and the underlying mechanisms that may contribute to the development of a nondipping nocturnal blood pressure profile in OSA patients. This topic is important in the context of the recent SAVE (Sleep Apnea Cardiovascular Endpoints) trial report [7] involving 2717 patients with established cardiovascular disease and moderate or severe OSA associated with minimal sleepiness who were randomised to best usual care with or without added continuous positive airway pressure (CPAP) therapy and followed for up to 7 years.…”
mentioning
confidence: 99%
“…Furthermore, hypertension is increasingly recognised as an important predictor of prevalent OSA and appears to be more predictive than excessive day-time sleepiness in some settings [5]. However, recent evidence also indicates that only moderate-severe OSA (AHI >20 events·h -1 ) constitutes a significant independent risk for hypertension [2] and cluster analysis of sleep clinic populations indicates that particular population subtypes are especially associated with hypertension [6].…”
mentioning
confidence: 99%